PENGARUH PEMBERIAN LAYANAN INFORMASI TENTANG CARA BELAJAR EFEKTIF DAN EFISIEN TERHADAP MOTIVASI BELAJAR SISWA KELAS XI IPA SMA MUHAMMADIYAH SATU PEKANBARU TAHUN PELAJARAN 2013-2014 - Muhammad Zikri; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research aims to test the influence of service information about learn how to effectively and efficiently on motivation to learn. This research uses the draft research pre experiment design in the form of one group pre test-post test design. Data collection method using question form scale motivation to learn. The subject of this research is the grade XI IPA 3 and 4 Senior High School Muhammadiyah Satu. Statistical data analysis techniques using the parametric formula with t test. The results obtained from the calculation = 18,71, the next count with t the table level 5% with the degrees of freedom (df) 140 that amounted to 1,960 so 18,71>1,960. Then it can be inferred that there is a positive influence by providing information about how to learn effectively and efficiently to students' motivation.Keyword: information services, learn how to effectively and efficiently, motivation to learn.